Customary Marriage vs. Human Rights: Legal Challenges of Kawin Tangkap in Sumba, Indonesia - Firman Laia (Jurnal Mengkaji Indonesia, 2025)
Abstract: Marriage, as a social and legal institution, reflects the cultural values of a society. In Sumba, the practice of kawin tangkap (forced marriage by abduction) persists despite legal and human rights concerns. This practice, in which a man "captures" a woman to make her his wife, raises various issues, particularly regarding individual freedom and gender equality. Purpose: This study aims to analyze the practice of kawin tangkap in Sumbanese society from a human rights perspective and evaluate the legal protections for women subjected to this practice. Design/Methodology/Approach: This research employs a normative legal approach, incorporating legislative and conceptual analysis. It examines relevant legal frameworks and their interaction with customary law practices still observed in Sumba. Findings: The study finds that kawin tangkap contradicts Indonesia’s positive law, including the Criminal Code (KUHP), Law No. 35/2014, and Law No. 12/2022. Furthermore, this practice violates human rights instruments such as the Universal Declaration of Human Rights (UDHR) and the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW). A key challenge in addressing kawin tangkap lies in the disparity between customary law and state law, which complicates law enforcement within indigenous communities. Originality/value: This study provides new insights into how national law can adapt to local traditions without compromising human rights protections. It also offers strategic recommendations for harmonizing customary law with positive law to uphold justice for women in indigenous communities.